Digital doorstep banking: Female banking agents lead digital financial inclusion through the pandemic and beyond - Alreena Renita Pinto; Amit Arora (Asian Development Bank Institute (ADBI), 2021)
This paper discusses the business correspondent (BC)-agent banking model in India against the backdrop of community-based rural livelihood programs, its relevance in facilitating financial inclusion in underserved rural geographies, and its potential to address the gender gap in financial inclusion. In recent years, India has made significant progress toward financial inclusion with the support of technological and policy innovations, but there remains a gap in access to basic banking services for women, particularly rural women. The launch of the Pradhan Mantri Jan Dhan Yojana (PMJDY) in 2014 resulted in the opening of 420 million bank accounts, of which 53.26% belonged to women, though surveys have suggested that almost 55% of women remained registered inactive users. The World Banksupported rural livelihood programs in India have been instrumental in the institutional strengthening of 6.9 million women's self-help groups (SHGs) and have facilitated their access to savings and credit to the tune of US3.7 billion (INR260 billion) and US56 billion (INR3600 billion), respectively, while creating an ecosystem for the deployment of female members as BC agents across rural India. The paper uses a gender and technology lens to explore the role of female banking agents in facilitating access to social security transfers using fingerprint-based biometric authentication solutions during the nationwide pandemicrelated lockdown in India between March 2020 and July 2020. Using data from multiple small samples of banking agents, this paper describes the on-the-ground challenges observed in the provision of basic banking services to access cash transfers during the pandemic. Extrapolating from this experience, the paper makes a case for strengthening the agent banking ecosystem, improving the delivery architecture for direct benefit transfers (DBTs), encouraging competition between banking service providers, and providing demand-based financial products and services to expand gender-focused financial inclusion further.
Keywords: G21; G23; G28; G29; 330; Financial inclusion; gender; agent banking; India